Diversity, domination and behavior of mosquitoes in filariasis endemic area of Bogor District, West Java, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Nirwan M, Hadi UK, Soviana S, Satrija F, Setiyaningsih S. 2022. Diversity, domination and behavior of mosquitoes in filariasis endemic area of Bogor District, West Java, Indonesia. Biodiversitas 23: 2093-2100. A study on the diversity, dominance and behavior of mosquitoes was done in the two filariasis endemic areas in Bogor District, West Java, Indonesia. The objectives of this study were to determine the diversity, dominance and behavior of mosquitoes and their importance as vectors of filariasis in two endemic areas in Bogor District, namely Tamansari Village (rural) and Cimanggis Village (urban). This research was carried out from September 2019 to February 2020. Mosquitoes were collected from 6.00 pm to 6.00 am, twice a month in each village, by using the bare leg collection technique. The collected mosquitoes were identified and analyzed. Filaria detection was carried out by dissecting technique and polymerase chain reaction (PCR). The result indicated eight (8) species of mosquitoes in the rural area (Tamansari village), i.e., Culex quinquefasciatus, Aedes aegypti, Cx. vishnui, Cx. tritaeniorhynchus, Armigeres kesseli, Ar. subalbatus, Ae. albopictus, Mansonia annulata. On the other hand, there were six (6) species found in the urban area (Cimanggis village), i.e., Cx. quinquefasciatus, Ae. aegypti, Ar. kesseli, Ar. subalbatus, Cx. vishnui, Cx. tritaeniorhynchus and Cx. quinquefasciatus were found to be the most dominant in Tamansari village (90.46) and also in Cimanggis Village (95.67). Based on the analysis showed that the mosquito diversity index was low in both the Tamansari village (H’: 0.444) and the Cimanggis village (H’: 0.238). In general, mosquito-biting behavior prefers to suck blood indoors (anthropophilic) with a peak density in the range of 23.00-04.00. The results of filarial detection using dissecting technique and PCR methods against mosquitoes caught in Tamansari Village and Cimanggis Village did not find any L3 larvae and microfilariae in the examined mosquitoes. Culex quinquefasciatus was found to be very potential as the main vector for the spread of filariasis both in rural and urban areas of endemic filariasis of Bogor District, Indonesia.
Keywords: Behavior, diversity, dominance, filariasis endemic, mosquitoes